Optical pumping of dense charge-exchange targets for polarized Ion sources - Cornelius,WD; Taylor,DJ; York,RL; Hinds,EA (Physical Review Letters, 1982)
Optical pumping by a single-frequency cw ring dye laser of thick sodium vapor targets (NL>1013 atoms/cm2) without buffer gas has been investigated for application in a polarized ion source. The atomic polarization of the sodium was determined from the optical rotation of a second dye laser tuned midway between the D lines. Rate-equation calculations reproduce the experimental data and predict very high polarizations (P>~0.8) with the use of one or more single-frequency dye lasers in thick alkali-metal vapor targets. © 1982 The American Physical Society.